Aspergillus fumigatus native valve infective endocarditis in an otherwise healthy adult. Issue 2 (18th February 2016) - Ikediobi, Uchenna; Sutton, Richard E.
Abstract : Introduction: Fungal endocarditis is a rare cause of infective endocarditis, and Aspergillus spp. account for up to 30 % of all cases. Risk factors include intravenous drug use, immunosuppression, malignancy and the presence of prosthetic valves. Case presentation: We present a case of A. fumigatus endocarditis in a patient without any known or described risk factors. Conclusion: Diagnosis of Aspergillus endocarditis requires a high clinical index of suspicion, given the initial non-specific presentation, and treatment may require both medical and surgical therapies to ensure improved outcomes, but mortality rates still approach 80 %. Voriconazole remains the antifungal agent of choice.